Effect of high sodium ion level on the interaction of AmB with a cholesterol-rich phospholipid monolayer - Wang, Juan; Qiang, Jiahao; Li, Jinzi; Wang, Dengwu (Frontiers in Molecular Biosciences, 2024)
Invasive fungal infections are a primary reason for high mortality in immunocompromised people, especially in critically ill patients, such as intensive care unit (ICU) patients, advanced cancer patients, or severe burn patients. Hypernatremia also can increase mortality in severely ill patients. Amphotericin B (AmB) is the gold standard for treating infections, but in severely ill patients, AmB can cause hematotoxicity when administered intravenously due to its interaction with cholesterol on red blood cell membranes. This results in limited doses of AmB and affects the treatment of infections. The proportion of cholesterol molecules in membrane lipids in red blood cells is as high as 50 mol%, and the sodium ions can influence the interaction between AmB and lipids on the membrane. Therefore, in the complex clinical situation of a severely ill patient with a fungal infection and hypernatremia, the interaction between amphotericin B and the red blood cell membranes is worth studying in depth. In this work, the interaction between AmB and the dipalmitoyl phosphatidylcholine (DPPC)/cholesterol mixed monolayer in the presence of high sodium ion levels was studied when the proportion of cholesterol was 50%. The results show that the effect of AmB on reducing the monolayer’s area at a high level of sodium ions is slightly stronger at 30 mN/m. The effect of AmB on reducing the elastic modulus of the DPPC/Chol monolayer is significantly weakened by a high sodium ion level, compared with the level of sodium ions at normal physiological concentration. The higher the sodium ion concentration, the weaker the intermolecular force of the DPPC/Chol/AmB mixed monolayers. The scanning electron microscope (SEM) and atomic force microscopy (AFM) observations suggest that at a high sodium ion level, the presence of AmB significantly reduces the surface roughness of the DPPC/Chol monolayer. AmB may bind to cholesterol molecules, and it isolates cholesterol from the monolayer, resulting in a reduced height of the cholesterol-rich monolayer and an increasingly dispersed monolayer region. The results are beneficial to understanding the mechanism of impact of a high sodium ion level on the relationship between AmB and red blood cell membranes rich in cholesterol and are valuable for understanding the hemolytic toxicity of AmB to red blood cells at a high sodium ion level.